Sinema Terbuka Sebagai Ruang Ketiga di Jakarta - Tramilia Salsabila Utami; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Cinema in Jakarta generally located in a shopping mall in Jakarta. Cinema nowadays becomes a destination for people but not yet become a third place. The lack of third place in Jakarta that can provide a place for gathering, as a meeting point, and entertainment makes Jakarta residents used commercial building as a third place. Looking at the design and program a cinema that can meet the conditions and characteristics of a third place by looking at the phenomenon cinema in Jakarta. Open cinema takes layar tancap concept or "misbar" that have been established in Indonesia. The purpose of layar tancap is to give an entertainment in areas that are difficult to reach, apparently can be applied in the city. Under the discussion, a cinema should be able to become the third place so that makes the visitor feel comfortable, with the main activity is watching a movie. Open cinema is expected to become a third place that can provide entertainment watching a movie in Jakarta without having to come to a cinema in a shopping center. Cinema that can become a third place in Jakarta. Giving a cinema with a different atmosphere, trying to give space for people to interact while providing entertainment. Keywords: Entertainment; Open Cinema; Third place AbstrakBioskop di Jakarta umunya berada di dalam pusat perbelanjaan besar di Jakarta. Bioskop saat ini menjadi tujuan namun belum menjadi sebuah third place. Minimnya third place di Kota Jakarta yang dapat memberikan wadah untuk berkumpul, titik temu, dan menyediakan sebuah hiburan membuat warga Jakarta menjadikan bangunan komersil sebuah third place. Bagaimana desain dan program sebuah bioskop yang dapat memenuhi syarat dan ketentuan sebuah third place dengan melihat fenomena bioskop di Jakarta saat ini. Open cinema atau sinema terbuka mengambil konsep layar tancap atau misbar yang dari dulu sudah ada di Indonesia. Layar tancap yang tujuan utamanya adalah untuk memberikan hiburan di daerah yang sulit dijangkau ternyata dapat diterapkan di kota besar. Dalam pembahasan sebuah bioskop seharusnya dapat menjadi ruang ketiga sehingga dapat membuat penggunanya merasa nyaman, dengan memberikan aktivitas utama menonton film. Open Cinema diharapkan dapat menjadi third place yang dapat menyediakan hiburan menonton di Jakarta tanpa harus datang ke bioskop di pusat perbelanjaan kota seperti bioskop saat ini. Open Cinema dapat menjadi sebuah third place di kota Jakarta, yang memberikan hiburan menonton dengan suasana yang berbeda, berusaha memberikan ruang hiburan dan interaksi bagi masyarakat.